Molecular imaging of proteins in tissues by mass spectrometry - Seeley, Erin H; Caprioli, Richard M (Proceedings of the National Academy of Sciences - PNAS, 2008)
Imaging MS (IMS) is an emerging technology that permits the direct analysis and determination of the distribution of molecules in tissue sections. Biological molecules such as proteins, peptides, lipids, xenobiotics, and metabolites can be analyzed in a high-throughput manner with molecular specificity not readily achievable through other means. Tissues are analyzed intact and thus spatial localization of molecules within a tissue is preserved. Several studies are presented that focus on the unique types of information obtainable by IMS, such as Abeta isoform distributions in Alzheimer's plaques, protein maps in mouse brain, and spatial protein distributions in human breast carcinoma. The analysis of a biopsy taken 100 years ago from a patient with amyloidosis illustrates the use of IMS with formalin-fixed tissues. Finally, the registration and correlation of IMS with MRI is presented.